Innovative Endeavors and Economic Development from the Regional Perspective - Majka, Agnieszka; Jankowska, Dorota (Regional Barometer. Analyses & Prognoses, 2018)
The paper discusses innovation-related issues as being factors of economic development of voivodships. The first part takes a close theoretical look at the essence of innovation and economic development, while highlighting the impact of innovation and innovativeness on regional socio-economic development. The second part is devoted to empirical application of taxonomic methods in ordering of objects to enable the ranking of voivodships regarding their levels of innovation and economic development. This part of the article is an attempt to evaluate the mutual dependency of both rankings of Poland voivodships. The objective of the current study is to determine the ranking of Poland’s voivodships in respect of their levels of economic innovativeness, and economic growth as well as to evaluate the relationship between both phenomena.